HUBUNGAN ANTARA TINGKAT PENGETAHUAN IBU BALITA TENTANG GIZI DENGAN STATUS GIZI BALITA (1-5 TAHUN) DI POSYANDU DUSUN MODOPURO DESA MODOPURO KECAMATAN MOJOSARI MOJOKERTO - Zakiyah, Ana (Jurnal Keperawatan Bina Sehat, 2012)
Knowledge factor can influence the nutrient status of individual or group. A mother who is as manager and caretaker of meals in family has essential role in determining the nutrient status of family member. Children under five years old need different nutrient from adult. Mother should give more attention on their nutrient needed because they are in golden age period. The purpose of research is to know the correlation between the knowledge level of children under five years old’s mother about nutrient with nutrient status of children under five years old in posyandu dusun Modopuro desa Modopuro kecamatan Mojosari kabupaten Mojokerto. The research design is Analytic corelational with Cross Sectional Approach. And the population of this research is all mother who have children under five years old in posyandu Modopuro desa Modopuro kecamatan Mojosari kabupaten Mojokerto amount 163 people, by using simple random sampling, it gets 70 people as research sample. The independent variable is the knowledge level of mother about nutrient and the dependent variable is the nutrient status of children under five years old. The data are collected using questionnaires and dacin (weight scales). Then, data analysis is held and statistic checking with spearman Rho the supported by SPSS version 16,0 and the result shows that  (0,000). So,  < indicates H0 is rejected. It can be concluded that there is correlation between the knowledge level of children under five years old’s mother about nutrient and nutrient status of children under five years old. If the children under five years old’s mother have a good knowledge about nutrient so the nutrient status of children under five years old be good nutrient status too. Mother should give more attention in every meals that are served for their family. Moreover, if there is mother who have children under five years old. It is because nutrient for them are different from adults. Mother also should be provide knowledge and skills in managing healthy meals. Keywords: knowledge, mother, nutrient status of children under five years old.,